Gathering and sharing Web-based information: Implications for "ePerson" concepts - Hyams, Jennifer; Sellen, Abigail (Hewlett-Packard Labs Technical Report, 2003)
“EPerson” is an example from HP Labs of the kind of new ideas for knowledge management and sharing that are being inspired by Peer-to-Peer and Semantic Web technologies. To help inform and ground the efforts of such developments we report on a study looking at how people gather and share information using today’s digital tools. We look at 16 knowledge workers’ use of the Web, examining the lifecycle of this information and the way in which it is shared. We find that Peer-to-Peer knowledge sharing is different to say Peer-to-Peer music sharing, user’s PC’s being more like “workbenches” than archives. We also find that people learn through the process of gathering, creating and organising their information. Such knowledge enables ind ividuals to reuse and share their information, personally owned information always being modified or enriched before sharing. Such insights provide important implications for developing Peer-to-Peer file sharing technologies which we discuss.